Disaster management - Kanwar, Rakesh (2001)
Disaster Management is the latest buzzword in the country. The Gujarat earthquake has jolted the nation. After the quake everyone started talking about poor management of disaster situations and the need to have a proper disaster management plan. Newspapers were full of articles, editorials and special stories for quite sometime. As soon as they got the next big story they moved on. But that is the character of the media. Irony is that the issues highlighted by the media and other experts tend to be forgotten. Nothing can highlight it better than the national apathy and indifference in the intervening period between Orissa Cyclone and Gujarat Earthquake. The paper takes a look at the disaster management scenario in the country and advocates an integrated approach to disaster management that focuses on fire prevention rather than fire fighting, besides seeking to involve local people through elected bodies at all levels of governance. The paper also attempts to pin point the problem areas in disaster management and the lack of proper planning in the spheres of disaster prevention, mitigation and post situation management. - Reproduced.
Keywords: Disasters